Pengaruh Beda Suhu Peletakan Bangkai terhadap Pertumbuhan Larva Lalat Chrysomya Megacephala Pada Tikus Wistar (Rattus norvegicus) - Andi Ipaljri Saputra; Isramilda Isramilda; Sufyan Ats Tsaury (Universitas Batam, 2022)
Background: Not a few phenomena of abandoned corpses without knowing the length of time of death, to reveal the mystery of abandoned corpses, identification is needed in order to find out post-mortem interval (PMI). With the help of forensic entomologists as investigators and Chrysomya Megacephala flies as the type of animal that first landed on the corpse. The fast or slow growth of flies is also influenced by temperature as the main factor, so by examining the growth of flies with different temperatures, it is possible to calculate the length of time the corpse will die. Methods:This research method is an analytical research true experimental design in the laboratory using the